2017
DOI: 10.1021/acs.chemrestox.6b00407
|View full text |Cite
|
Sign up to set email alerts
|

Isotope Dilution nanoLC/ESI+-HRMS3 Quantitation of Urinary N7-(1-Hydroxy-3-buten-2-yl) Guanine Adducts in Humans and Their Use as Biomarkers of Exposure to 1,3-Butadiene

Abstract: 1,3-Butadiene (BD) is an important industrial and environmental chemical classified as a known human carcinogen. Occupational exposure to BD in the polymer and monomer industries is associated with an increased incidence of lymphoma. BD is present in automobile exhaust, cigarette smoke, and forest fires, raising concern about potential exposure of general population to this carcinogen. Following inhalation exposure, BD is bioactivated to 3,4-epoxy-1-butene (EB). If not detoxified, EB is capable of modifying gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(58 citation statements)
references
References 52 publications
1
57
0
Order By: Relevance
“…Our previous experience with developing methods to quantify urinary DNA adducts showed that SPE alone does not result in sufficient sample purity for nanoLC/MS analyses [ 36 ]. Therefore, following SPE, samples were further purified using an offline HPLC method [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Our previous experience with developing methods to quantify urinary DNA adducts showed that SPE alone does not result in sufficient sample purity for nanoLC/MS analyses [ 36 ]. Therefore, following SPE, samples were further purified using an offline HPLC method [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…Earlier studies have described urinary DNA adducts induced by endogenous biomolecules such as estrogens [ 55 ], lipid peroxidation products [ 56 ] as well as by reactive exogenous metabolites such as styrene [ 57 ] and polyaromatic hydrocarbons [ 58 ]. Previous studies employed BD-derived urinary adduct, EB-GII, as a useful biomarker of exposure to BD and metabolic activation [ 34 , 35 , 36 , 59 ]. However, EB-GII is formed from BD monoepoxide (EB) and thus does not reflect the formation of the most genotoxic metabolite of 1,3-butadiene (i.e., DEB).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The DNA adducts released are eventually excreted in urine and thus can also be used as urinary biomarkers. Although many BD-derived DNA adducts have been identified [ 7 ], so far only two DNA adducts, N 7-[1-​(hydroxymethyl)​-​2-​propen-​1-​yl]guanine (EB-GII) and 1,4- bis (gua-7-yl)-2,3-butanediol ( bis -N7G-BD), have been used as urinary biomarkers [ 130 , 131 ].…”
Section: Introductionmentioning
confidence: 99%